Effects of Gracilaria Changii Extract Onapoptosis snd Gene Expression of Mcf-7and Mda-Mb-23 1 Breast Cancer Cell Lines - Abdul Hamid, Nazefah (2006)
Cancer is a large group of diseases characterized by uncontrolled growth and spread of abnormal cells. Hundreds of research studies have demonstrated significant benefit of the use of natural products in the treatment of cancer and scientists believe examining new natural products will continue to turn up even more useful drugs to treat cancer. Marine organisms are a rich source for natural products and many compounds that are derived from these have generated interest for their cytotoxicities. Gracilaria changii is a type of red seaweed which comes from the family Rhodophyta. It is a relatively abundant seaweed in Malaysia can be found in the mangrove areas. In this study, the chemotherapeutic potential of Gracilaria changii in selected reproductive cancer cell lines was evaluated together with tamoxifen, a commercially used drug in cancer treatment. Exposure of breast, ovarian and cervical cancer cell lines, to a range of Gracilaria changii extracts demonstrated growth inhibition in some of these cancer cells in a dose-dependent manner. The Gracilaria changii extracts received from Kolej iii Universiti Sains dan Teknologi Malaysia (KUSTEM) were methanol, buthanol and diethyl ether extracts. The methanol extract gave the most promising ICso values, as determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay and the results are as follows: MCF-7 (7.8 pglml), MDA-MB-23 1 (25 pglml) HeLa (70.26 pglml) and Caov-3 (90.46 pglml). Since the results for the breast cancer cell lines were significant compared to the ovarian and ceivical cancer cell lines, they were chosen for further analysis. The normal breast cell line, MCF-1OA was also tested and the ICjo value was found to be > 1000 pglml, indicating that the methanol extract was not cytotoxic to normal cells. AOPI staining was used to study the morphology of the cells treated with the extract. Apoptotic features that included membrane blebbing and nucleus condensation were evident in MCF-7 and MDA-MB- 23 1 cancer cells. Subsequently, the TUNEL assay was conducted to determine and quantitate the apoptotic cells within a cell population. The results suggest that the methanol extract was better of inducing cell death by stimulating apoptosis than tamoxifen. This is based on the significantly higher percentage of apoptotic cells in the G.cl7utzgii methanol extract treated cancer cells as compared to tamoxifen. For MCF-7 and MDA-MB-23 1 cell lines, p was <0.01 when compared with control (24 hours) and P of <0.001 when compared with control for 48 hours. In addition, gene expression analysis was performed using the microarray technology. This technology which allows the simultaneous analysis of a large number of nucleic acid hybridization experiments and was cal~iedo ut to determine the gene expression profile. Preliminary work on micorarray was conducted using MCF-7 cell line only, due to time constraints and limited funding. Upon treatment with the methanol extract on MCF-7, several suppressed genes were identified including haplotype nlb mitochondrion complete genome, melanomaassociated antigen p97 isofonn 1 and damage-specific DNA binding protein 2 (ddb2). The results showed that the three genes regulated by the methanol extract encode proteins . that belongs to DNA repair, protection against membrane-lipid peroxidation and maternal inheritance family, which may play an important role for the cancer treatment. It was hrther confirmed using Reverse Transcription Polymerase Chain Reaction (RT-PCR). Therefore, the methanol extract of Gracilaria chaizgii is a potential candidate to be d-ev eloped as a chemotherapeutic agent in the treatment of estrogen receptor-positive breast cancer